2013
DOI: 10.1007/s12288-013-0229-4
|View full text |Cite
|
Sign up to set email alerts
|

Blood Transfusion Practice in Obstetric and Gynecology: Impact of Educational Programs to Create Awareness for Judicious Use of Blood Components

Abstract: The study presents the data analysis (1) To find out the trend of blood component use during the period 2003-2010 and to determine impact of component awareness programs on reduction in whole blood (WB) and single unit transfusions. (2) To determine Hb trigger. The details about blood units issued were entered in the integrated blood bank management software as well as in Microsoft Excel. The data of 4,838 cases of pregnancy anemia; 2,244 receiving blood for obstetric (Ob) hemorrhage including 270 cases of dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The overall blood transfusion rate in this study accounts for 7.8%, which correlates with other similar studies conducted in India. 5 Although the goal of modern transfusion practice is to provide appropriate replacement therapy with required components, 10 34.6% of whole blood transfusion was observed in Phase 1, of which 43.2% is accounted for in the management of chronic anemia ( Table 3 ). It is important to be aware that whole blood transfusion carries the risk of volume overload in chronic anemia patients and is indicated only in the management of acute blood loss, if components are unavailable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The overall blood transfusion rate in this study accounts for 7.8%, which correlates with other similar studies conducted in India. 5 Although the goal of modern transfusion practice is to provide appropriate replacement therapy with required components, 10 34.6% of whole blood transfusion was observed in Phase 1, of which 43.2% is accounted for in the management of chronic anemia ( Table 3 ). It is important to be aware that whole blood transfusion carries the risk of volume overload in chronic anemia patients and is indicated only in the management of acute blood loss, if components are unavailable.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Parker et al, a low hemoglobin level, in the absence of symptoms, was reported as the most common reason for red cell transfusion, while other studies in the literature have documented different reasons for the inappropriate use of packed red blood cells. 5 , 11 , 12 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Therefore clinicians must prevent single unit transfusion in adult patients which can raise Hb only by 1-1.5g/dL. 10 WHO strongly discourages single unit transfusion. 11 The practice of single unit transfusion is largely avoidable.…”
Section: Resultsmentioning
confidence: 99%
“…Life of Dr. H. M. Bhatia (1928–1988) has been briefly recorded in his obituary,[ 1 ] and recently in a biographical sketch. [ 2 ]…”
mentioning
confidence: 99%